2022
DOI: 10.1002/pca.3198
|View full text |Cite
|
Sign up to set email alerts
|

MS/MS molecular networking‐guided in‐depth profiling of triterpenoid saponins from the fruit of Eleutherococcus senticosus and their neuroprotectivity evaluation

Abstract: Introduction: Eleutherococcus senticosus fruit (ESF) is a natural health supplement resource that has been extensively applied as a tonic for the nervous system. The structures and neural bioactivities of triterpenoid saponins (TS), which are the major constituents of ESF, have not been comprehensively analyzed thus far.Objective: We conducted a complete in-depth MS/MS molecular networking (MN)based targeted analysis of TS from the crude extract of ESF and investigated its neuroprotective value.Methods: An MS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…In the European Union, ES has been used for more than 40 years, the European Medicines Agency listed ES root as an herb that can treat symptoms such as fatigue in 2014, and in the 14th edition of the Russian Pharmacopoeia, there is also a monograph on ES (Shikov et al., 2021 ). Modern pharmacological studies have shown that various components of ES have been widely used in traditional medicine, including root, bark, leaf, and fruit, and they have several pharmacological activities, such as antioxidant, anti‐inflammatory, and treatment of neurodegenerative diseases (Jiang & Wang, 2015 ; Kim et al., 2020 ; Xia et al., 2020 ; Zhou et al., 2023 ). And most importantly, ES is an adaptogen, and the extract of this natural plant acts as an adaptogen to improve the adaptability, resilience, and survival rate of organisms to stress (Gerontakos et al., 2020 ; Panossian et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the European Union, ES has been used for more than 40 years, the European Medicines Agency listed ES root as an herb that can treat symptoms such as fatigue in 2014, and in the 14th edition of the Russian Pharmacopoeia, there is also a monograph on ES (Shikov et al., 2021 ). Modern pharmacological studies have shown that various components of ES have been widely used in traditional medicine, including root, bark, leaf, and fruit, and they have several pharmacological activities, such as antioxidant, anti‐inflammatory, and treatment of neurodegenerative diseases (Jiang & Wang, 2015 ; Kim et al., 2020 ; Xia et al., 2020 ; Zhou et al., 2023 ). And most importantly, ES is an adaptogen, and the extract of this natural plant acts as an adaptogen to improve the adaptability, resilience, and survival rate of organisms to stress (Gerontakos et al., 2020 ; Panossian et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent experiments have isolated new oleanane‐type triterpenoid saponins and sesquiterpenoids from ESF, and demonstrated that these new compounds have certain activities in cells (Zhang et al., 2021 ). In addition, a comprehensive and in‐depth mass spectrometry analysis and cleavage regularity of triterpenoid saponins in ESF have been conducted, proving that triterpenoid saponins in ESF can significantly reduce the damage of β‐amyloid‐induced neural network and play a neuroprotective role (Zhou et al., 2023 ). Bioactive compounds have also been found in rat sera after ESF administration (Han et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%